Community Structure of Hard Coral (Scleractinia) in the Walenekoko Reef Flat, Pasir Panjang, Bitung City - Pratiwi, Utary; Kambey, Alex D.; Lalamentik, Laurentius Th. X.; Tilaar, Ferdinand Frans; Mandagi, Stephanus Vianny; Manembu, Indri S. (Sam Ratulangi University, 2022)
Coral reefs are one of the potential good water resources in Indonesian marine waters. Ecologically, coral reefs can only develop in tropical climates. Hard coral is one of the important components as a constituent of coral reef ecosystems and plays an important role for marine biota. The research was conducted at the reef flat of Walenekoko Village, Pasir Panjang Village, South Lembeh District, Bitung City. The research covers the species, family and life form composition, and ecological indices (diversity, species equitability, and dominance indices). The research was carried out with an Underwater Photo Transect (UPT) method. The results obtained 18 types of hard corals belonging to 5 families. Montipora samarensis was the most abundant coral in the area with 43% of the community composition. The Faviidae family and Acroporidae (33%) had the largest percentage in all transects. The form of coral growth consisted of Acropora Submassive (ACS) 53%, Coral Massive (CM) 30%, and for Acropora Branching (ACB) 16%. The highest diversity value is at point 3 of 1.64, and point 1 of 1.60, while the lowest is at point 2 of 0.56. The evenness index obtained at point 1 is 0.70, and at point 2 is 0.30. The dominance values obtained ranged from 0.25 to 0.52.Keywords: Community Structure; Hard Coral; Reef FlatAbstrakTerumbu karang merupakan salah satu potensi sumberdaya perairan yang baik di perairan laut Indonesia. Secara ekologis terumbu karang hanya dapat berkembang di wilayah beriklim tropis. Karang keras merupakan salah satu komponen penting sebagai penyusun ekosistem terumbu karang dan berperan penting bagi biota laut. Penelitian ini dilakukan di rataan terumbu Desa Walenekoko, Desa Pasir Panjang, Kecamatan Lembeh Selatan, Kota Bitung. Penelitian meliputi komposisi spesies, famili, dan bentuk kehidupan, serta indeks ekologi (keanekaragaman, keseragaman spesies, dan indeks dominasi). Penelitian dilakukan dengan metode Underwater Photo Transect (UPT). Hasil penelitian diperoleh 18 jenis karang keras yang termasuk dalam 5 famili. Montipora samarensis adalah spesies yang paling banyak ditemukan di daerah tersebut dengan persentase 43%. Famili Faviidae dan Acroporidae (33%) memiliki persentase terbesar di semua transek. Bentuk pertumbuhan karang terdiri dari: Acropora Submassive (ACS) 53%, Coral Massive (CM) 30%, dan untuk Acropora Branching (ACB) 16%. Nilai keanekaragaman tertinggi yaitu pada titik 3 sebesar 1,64, dan titik 1 sebesar 1.60, sedangkan yang termasuk rendah yaitu pada titik 2 sebesar 0,56. Indeks kemerataan diperoleh pada titik 1 sebesar 0,70, dan pada titik 2 sebesar 0.30. Nilai dominasi diperoleh berkisar antara 0.25 hingga 0.52.Kata kunci: Struktur Komunitas; Karang Keras; Rataan Terumbu.